Analyzing The Reasons Behind Suhento Liauw's Rejection On Theological Seminary Accreditation - Julitinus Harefa; Meniati Hia; Daniel Ari Wibowo (Theological Journal Kerugma, 2022)
Since the enactment of accreditation regulations within the Theological College, there have been Christian groups that have rejected the Theological College Accreditation on theological grounds or the principles of belief held. This Christian sect has established Theological Colleges in Jakarta and West Kalimantan and even holds graduations and issues diplomas and gives academic degrees to graduates, even though they have never submitted an accreditation form to BAN-PT (National Accreditation Board-University). Then how is the existence of this Theological College in the eyes of law and education in Indonesia and the theological response based on the beliefs of the Christian faith? To answer this question, in writing this article the author conducts library research to describe the logical consequences for the Theological College Institutions that do not heed the accreditation activities.